ANALYSIS OF CORE CONFIGURATION FOR CONCEPTUAL GAS COOLED FAST REACTOR (GFR) USING OPENMC - Iklimatul Karomah; Ahmad Muzaki Mabruri; Ratna Dewi Syarifah; Nuri Trianti (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2023)
This study focused on a conceptual core configuration of Gas Cooled Fast Reactor (GFR), as part of a generation IV reactor. Uranium-plutonium carbide (UC-PuC) was used as reactor fuel and a Monte Carlo simulation method using OpenMC has been carried out. This study aims to find the composition of uranium-plutonium carbide fuel to use inside a fuel pin, making up a hexagonal prism fuel assembly arranged to form an entire core. A homogeneous and heterogeneous core configuration was considered in this study, while the plutonium percentage varied from 8%- 15%. For the homogenous core configuration, 10% was found as the optimum plutonium fraction with the value of %∆k/k =1, which was then used as a reference to make up a heterogeneous core configuration. A heterogeneous core with 3 radial fuel regions of F1 using 9% Pu fraction, F2 10%, and F3 11% showed the most stable result for 5-year burn-up with a %∆k/k of 0.7. The %∆k/k value was decreased by 0.3 due to the fission reaction that occurred more evenly in all 3 fuel regions of heterogeneous configuration, reducing the core power peaking factor. Keywords: Core configuration, GFR, OpenMC, Reactivity, Fission reaction